2019
DOI: 10.1039/c9ob01415b
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic asymmetric spirocyclization reactions of cyclic 2,4-dienones with cyanoketones: synthesis of spiro-dihydropyrano cyclohexanones

Abstract: The first organocatalytic asymmetric synthesis of spiro-dihydropyrano cyclohexanones has been developed via the cascade reaction between cyanoketones and cyclic 2,4-dienones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Following the work of Ye and colleagues about the enantioselective 1,6-addition/1,4-addition cascade process (Scheme 24), the group of Pan applied the same strategy to the synthesis of spiro-dihydropyrano cyclohexanones (Scheme 28). [54] Their investigation began with the optimization of the reaction conditions realized on the dienone derivative 91 a (R 1 = Ph) and the compound 92 a (R 2 = Ph), which led to the selection of the Cinchona-based primary amine cat-32 as a catalyst. The use of diamine derivatives, such as compound cat-38 enabled the preparation of the desired compound with drastically lower enantiomeric excesses.…”
Section: Catalysis With Cinchona-derived Organocatalystsmentioning
confidence: 99%
“…Following the work of Ye and colleagues about the enantioselective 1,6-addition/1,4-addition cascade process (Scheme 24), the group of Pan applied the same strategy to the synthesis of spiro-dihydropyrano cyclohexanones (Scheme 28). [54] Their investigation began with the optimization of the reaction conditions realized on the dienone derivative 91 a (R 1 = Ph) and the compound 92 a (R 2 = Ph), which led to the selection of the Cinchona-based primary amine cat-32 as a catalyst. The use of diamine derivatives, such as compound cat-38 enabled the preparation of the desired compound with drastically lower enantiomeric excesses.…”
Section: Catalysis With Cinchona-derived Organocatalystsmentioning
confidence: 99%
“…Subsequent changes in temperature and the use of additives only slightly improved the ee value of the reaction. Fortunately, chiral N -Boc- l - t -leucine as an additive at 0 °C afforded the expected product in 83% yield with 90% ee and >20:1 dr, which were determined to be the best condition (Table , entry 20). Subsequent screening demonstrated that the significant enhancement of the target reaction yield by N -Boc- t -leucine ( d or l ) was based on the inhibition of the retro-Michael addition reaction after an extended period of time, and it can be attributed to its greater steric hindrance, which hinders its recombination with the reaction products.…”
mentioning
confidence: 99%